The Stability Comparison of Whitening Containing Kojic Acid and Glycolid Acid with The Same Cream Base - Siska Ferilda (Indonesian Journal of Pharmaceutical Research, 2021)
This study is an experimental study of stability of creams containing kojic acid and glycolic at 2% using the same cream base. Cream containing kojic acid and glycolic acid are often used as skin whitening. The cream made is observing changes in organoleptic properties, pH, viscosity and homogeneity in storage for 6 weeks. Observations of organoleptic properties including discoloration and cream odor, pH examination using pH meter, viscosity examination using viscometer Brookfield with a spindle speed of 20 rpm while for homogeneity examination using a metallograph with a magnification of 200x. The results showed that base creams and cream containing kojic acid showed better stability on organoleptic observations compared to cream containing glycolic acid. The pH of the cream containing kojic acid is less stable than the cream containing glycolic acid. Viscosity of cream containing kojic acid is more stable than cream containing glycolic acid. On homogeneity testing each cream looks homogeneous. In this study it can be concluded that cream containing kojic acid has better stability than cream containing glycolic acid.